2016
DOI: 10.12963/csd.16307
|View full text |Cite
|
Sign up to set email alerts
|

Articulatory Variability in 24- to 36-Month-Old Typically Developing Children

Abstract: Objectives:This study aims to investigate the articulatory variability of word and phoneme production on spontaneous utterance samples in typically developing children age 24 to 36 months. Methods: Speech samples were collected from 11 children age 24 to 30 months and 11 children age 31 to 36 months. Word variability, phoneme variability, percentage of consonants correct (PCC), and consonant inventory were measured. Eojeol was a basic unit for analysis of word variability. Both correct articulations and error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, it should be noted that researchers have reported on a lack of articulatory stability across children's speech sound productions and found high variability for children within this study's age group (see McLeod & Hewett [13]). While variability of productions may decrease with age (Holm et al, [11]), it does not entirely dissipate and may continue to limit the reliable use of independent measures across populations of young children as well as populations presenting with speech sound disorders [12].…”
Section: Consonants In Initial Word Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that researchers have reported on a lack of articulatory stability across children's speech sound productions and found high variability for children within this study's age group (see McLeod & Hewett [13]). While variability of productions may decrease with age (Holm et al, [11]), it does not entirely dissipate and may continue to limit the reliable use of independent measures across populations of young children as well as populations presenting with speech sound disorders [12].…”
Section: Consonants In Initial Word Positionmentioning
confidence: 99%
“…However, work with young children presents unique challenges to determining the consistent and reliable use of phonetic analyses due to variable word productions observed. The presence of normal articulatory variability complicates evaluation of speech sound production for young children (for an in-depth discussion see [11][12][13]). As noted above, Ferguson and Farwell [6], suggested that young children do not use phonemes as the minimal unit of lexical representation; rather, they organize with the syllable or word level as the minimal unit.…”
Section: Introductionmentioning
confidence: 99%
“…46 and has been noted by numerous researchers even for children with typical development. [46][47][48][49][50][51] The presence of intraword variability is particularly noticeable in the speech of 2-and 3-yearolds. 46,[49][50][51] While still observed in the speech of 3-year-olds, intraword variability tends to gradually decrease with age 51 making it a clinical consideration especially relevant to evaluating toddler speech sound productions.…”
Section: Current Limitations In Assessing Toddlers' Speech Sound Prodmentioning
confidence: 99%
“…The graph was represented as an adjacency matrix A, such that its value on row i and column j is Ai,j = w(i, j) (see equation (3)) if vertices i and j are adjacent in the graph, and 0 otherwise. The embedding into a low-dimensional space was found by solving the generalized eigenvalue problem…”
Section: Acoustic Analysesmentioning
confidence: 99%
“…Accuracy and variability have been measured in multiple ways. For example, accuracy traditionally is assessed using phonetic transcription by trained observers; these transcriptions can then be used to assess variability, by counting the number of different symbols that are used to transcribe multiple productions of the same target sound (e.g., [1], [2], [3]). Accuracy can also be measured in a more granular token-by-token basis by presenting multiple listeners with a word (or an excised syllable, etc.)…”
Section: Introductionmentioning
confidence: 99%